ASSISTANCE IN RELIGIOUS DEVELOPMENT OF THE SEBYAR MUSLIM COMMUNITY, SORONG REGENCY - Khatipah Khatipah; Aprilia Nurhayati; Irma Shintya; Miftahulfadlik Dabamona (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2022)
The Muslim community of the Sebyar Bintuni Tribe of Sorong Regency is one of the indigenous Papuan tribes that have long been residents of Sorong Regency with lack knowledge of Islamic teachings. This community empowerment program is desinged to carry out the planned program in order to solve various problems that have been experienced by the tribe. Participatory Action Research (PAR) is employed in this community service program through the development of the taklim assembly